Value-based Identification of Eco-effective Mitigation Options for Manufacturing Processes - Mindt, Nadja; Wiese, Mathias; Mennenga, Mark; Herrmann, Christoph (Procedia CIRP, 2024)
To avoid net greenhouse gases and decouple economic growth from resource use, manufacturers strive for solutions minimizing their emissions in operation whilst maximizing the perceived value to their customers offered by a product. One approach is the deployment of new manufacturing processes. The potential of these innovations is often limited to more eco-efficient solutions. However, current developments, e.g. global climate change and legal constraints, require engineering to broaden its focus on eco-effective solutions, covering function and system innovations and behavior change. Therefore, a methodology to identify eco-effective mitigation options for manufacturing processes is presented. By using the extended IPAT identity, the solution space for manufacturing processes to increase eco-effectiveness is highlighted. To consider behavior change, the concept of perceived value is embedded. The methodology is demonstrated on the example of additive manufacturing. The objective is to support engineers in identifying and evaluating market-relevant mitigation options for manufacturing processes addressing eco-effectiveness.